2020
DOI: 10.1108/aaaj-03-2019-3932
|View full text |Cite
|
Sign up to set email alerts
|

Contesting conformity: how and why academics may oppose the conforming influences of intra-organizational performance evaluations

Abstract: PurposeThe purpose of this paper is to develop a theoretical model elaborating on the type of conditions that can inhibit (or at least temporarily hold back) “reactive conformance” in the wake of an increasing reliance on quantitative performance evaluations of academic research and researchers.Design/methodology/approachA qualitative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 86 publications
3
20
0
Order By: Relevance
“…By contributing to previous literature, the present study is more concerned with the developing context (Egypt) and reveals this potential relationship by accrediting “intra-organisational” performance metrics within a single organisation (city council) to face the political demands and decisions for smart city governance. This further supports the recent study of Englund and Gerdin (2020), arguing for the importance of studying the conforming influences of intra-organisational performance evaluations to better understand their powerful roles within individual organisations (see also Alsaid and Ambilichu, 2020; Steccolini et al , 2020). To go one step further, the present study also revealed that the intra-organisational performance measurement system within the case (individual) organisation has been built on specific (accounting/accountability-based) metrics (integrating a blending of economic and social political performance measurements) rather than just mediating (technological and managerial) instruments as indicated previously in most institutional management accounting case studies on the relationship between performance measurement systems and smart city governance.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…By contributing to previous literature, the present study is more concerned with the developing context (Egypt) and reveals this potential relationship by accrediting “intra-organisational” performance metrics within a single organisation (city council) to face the political demands and decisions for smart city governance. This further supports the recent study of Englund and Gerdin (2020), arguing for the importance of studying the conforming influences of intra-organisational performance evaluations to better understand their powerful roles within individual organisations (see also Alsaid and Ambilichu, 2020; Steccolini et al , 2020). To go one step further, the present study also revealed that the intra-organisational performance measurement system within the case (individual) organisation has been built on specific (accounting/accountability-based) metrics (integrating a blending of economic and social political performance measurements) rather than just mediating (technological and managerial) instruments as indicated previously in most institutional management accounting case studies on the relationship between performance measurement systems and smart city governance.…”
Section: Discussionsupporting
confidence: 81%
“…But, its scope was extended to include the powerful role(s) of these “institutionalised” performance measurement systems or metrics in making and remaking political decisions and military actions in the city council. This further supports the most recent study of Steccolini et al (2020) arguing for the role(s) of accounting and performance measurement systems in contemporary public administration (see also Mutiganda et al , 2020; Englund and Gerdin, 2020; Noguchi et al , 2015). Clearly, this goes beyond the Dillard et al ’s (2004) framework which is limited to the cascading (macro-micro) institutionalisation process in organisations.…”
Section: Dillard Et Al’s (2004) Institutional Modelsupporting
confidence: 84%
See 2 more Smart Citations
“…Previous studies have also shown clear changes occurring in the performance measurement (PM) of universities. Among other topics, scholars have studied the assessment of academic performance (Argento et al, 2020), the use of key performance indicators (Guthrie and Neumann, 2007), research management (Agyemang and Broadbent, 2015), steering (Boitier and Rivi ere, 2013), and the measurement and evaluation of institutional and individual performance (Dobija et al, 2019;Kallio and Kallio, 2014;Ter Bogt and Scapens, 2012;Englund and Gerdin, 2019;Chatterjee et al, 2020;Martin-Sardesai et al, 2020;O'Connell et al, 2020a). A common factor in all these studies seems to be the transition in the studied organizations' institutional logic (IL) (Grossi et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%